Characteristics of Patients with Functioning Allograft over 10 Years in Deceased Donor Kidney Transplantation. (July 2018) - Kang, Seong Sik; Yeo, Sang Mok; Park, Hayeon; Park, Woo Yeong; Jin, Kyubok; Park, Sung Bae; Han, Seungyeup
Abstract : Introduction: The development of immunosuppressants improved the short-term outcomes of deceased donor kidney transplantation (DDKT), but the long-term survival rate was not. In the present study, we analyzed the clinical features of recipients with long-term allograft survival of over 10 years. Methods: The study included 127 recipients who received the first KT from DD at Keimyung University Dongsan hospital between October 1994 and June 2007. We compared the allograft survival group and the allograft loss group to evaluate risk factors for allograft loss. Results: The mean follow-up period was 163 ± 64 months. The 1, 5, and 10-year patient survival rate were 98.4 ± 1.1%, 95.9 ± 1.8%, and 92.5 ± 2.4%. The 1, 5, and 10-year allograft survival rate were 96.8 ± 1.6, 84.7 ± 3.2, and 65.5 ± 4.3%. Among the 127 recipients, 53 (41.7%) maintained allograft function for more than 10 years, and 58 (45.6%) lost allograft function. The allograft survival group had a significant higher ratio of using basiliximab (P < 0.001) and mycophenolate mofetil (MMF, P = 0.020). In addition, in the allograft survival group, incidence of rejection (P < 0.001) and infection (P = 0.020), and numbers of HLA DR mismatches (P = 0.028) were significantly lower. In multivariate Cox proportional hazards analysis, the use of MMF (hazard ratio [HR], 0.195; P = 0.002) decreased risk of allograft loss, and rejection was an independent risk factor for allograft loss (HR, 8.812; P < 0.001). Discussion: The allograft survival group showed higher allograft and patient survival rates. The major cause of graft loss was rejection, followed by patient death, recurrent glomerulonephritis and infection. And infection was a leading cause of patient death. To improve long-term clinical outcomes, it is important to maintain a balance between under- and over-immunosuppression. Conclusion: Recipients who maintained the allograft function for more than 10 years had a higher rate of MMF usage and fewer rejection episode. For long-term survival of the allograft kidney in DDKT, it is important to use appropriate immunosuppressants including MMF and prevent complications such as rejection and infection.